The Transformation of Library Management in Islamic University through Data-Driven Decision Making - Rodin, Rhoni; Hamengkubuwono, Hamengkubuwono; Fathurrochman, Irwan; Warlizasusi, Jumira (Corolla International Conference, 2025)
Libraries in Islamic Higher Education Institutions (IHEIs) hold a strategic role as centers for scientific information resources, the strengthening of Islamic literacy, and primary support for both learning and research processes. However, the challenges of the digital era, shifting patterns of information consumption, and demands for accountability necessitate a transformation in library management. This paper explores the application of the Data-Driven Decision Making (DDDM) approach in the management of IHEI libraries. Through a conceptual framework and literature review, this study analyzes how data related to user behavior, collection circulation, digital service utilization, and academic needs can serve as the basis for more objective, adaptive, and needs-oriented decision-making processes. DDDM promotes a paradigm shift in library management from reactive to proactive, integrating information technology into evaluation and strategic planning processes. Findings indicate that the implementation of DDDM can enhance service effectiveness, collection relevance, user engagement, and support IHEIs’ vision of producing academically and spiritually excellent graduates. This article also proposes implementation strategies, including the strengthening of library information systems, data literacy training for librarians, and the integration of libraries into digital academic systems. Therefore, data-based transformation becomes a crucial foundation for strengthening sustainable and future-oriented library management.